Predicting Survival After VA-ECMO for Refractory Cardiogenic Shock: Validating the SAVE Score - Faizan Amin, MD, FRCPC; Julia Lombardi, BSc; Mosaad Alhussein, MD, FRCPC; Juan Duero Posada, MD, FRCPC; Adrian Suszko, MSc; Margaret Koo, BSc; Eddy Fan, MD, PhD, FRCPC; Heather Ross, MD, FRCPC; Vivek Rao, MD, PhD; Ana Carolina Alba, MD, PhD; Filio Billia, MD, PhD, FRCPC (CJC Open, 2021)
Background: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is used increasingly to support patients who are in cardiogenic shock. Due to the risk of complications, prediction models may aid in identifying patients who would benefit most from VA-ECMO. One such model is the Survival After Veno-Arterial Extracorporeal Membrane Oxygenation (SAVE) score. Therefore, we wanted to validate the utility of the SAVE score in a contemporary cohort of adult patients. Methods: Retrospective data were extracted from electronic health records of 120 patients with cardiogenic shock supported with VA-ECMO between 2011 and 2018. The SAVE score was calculated for each patient to predict survival to hospital discharge. We assessed the SAVE score calibration by comparing predicted vs observed survival at discharge. We assessed discrimination with the area under the receiver operating curve using logistic regression. Results: A total of 45% of patients survived to hospital discharge. Survivors had a significantly higher mean SAVE score (–9.3 ± 4.1 in survivors vs –13.1 ± 4.4, respectively; P = 0.001). SAVE score discrimination was adequate (c = 0.77; 95% confidence interval 0.69-0.86; P < 0.001). SAVE score calibration was limited, as observed survival rates for risk classes II-V were higher in our cohort (II: 67% vs 58%; III: 78% vs 42%; IV: 61% vs 30%; and V: 29% vs 18%). Conclusions: The SAVE score underestimates survival in a contemporary North American cohort of adult patients with cardiogenic shock. Its inaccurate performance could lead to denying ECMO support to patients deemed to be too high risk. Further studies are needed to validate additional predictive models for patients requiring VA-ECMO. Résumé: Contexte: L’oxygénation extracorporelle veino-artérielle (ECMO-VA) est de plus en plus utilisée comme assistance pour les patients qui sont en choc cardiogène. En raison du risque de complications, des modèles de prédiction peuvent aider à déterminer quels patients bénéficieraient le plus d’une ECMO-VA. Le score SAVE (Survival After Veno-Arterial Extracorporeal Membrane Oxygenation) est un modèle de ce genre. Par conséquent, nous voulions valider l’utilité du score SAVE dans une cohorte contemporaine de patients adultes. Méthodologie: Des données rétrospectives ont été extraites de dossiers médicaux électroniques de 120 patients atteints d’un choc cardiogène ayant reçu une ECMO-VA entre 2011 et 2018. Le score SAVE a été calculé pour chaque patient afin de prédire la survie au congé de l’hôpital. Nous avons évalué la calibration du score SAVE en comparant la survie prédite au moment du congé et la survie observée. Nous avons évalué la discrimination par l’aire sous la courbe opérationnelle chez le receveur en faisant appel à la régression logistique. Résultats: Au total, 45 % des patients ont survécu au congé de l’hôpital. Les survivants affichaient un score SAVE moyen considérablement plus élevé (–9,3 ± 4,1 chez les survivants vs –13,1 ± 4,4; p = 0,001). La discrimination par le score SAVE était adéquate (c = 0,77; intervalle de confiance à 95 % : 0,69 à 0,86; p < 0,001). La calibration du score SAVE était limitée, car les taux pour les classes de risque II à V étaient plus élevés dans notre cohorte (II : 67 % vs 58 %; III : 78 % vs 42 %; IV : 61 % vs 30 %; et V : 29 % vs 18 %). Conclusions: Le score SAVE sous-estime la survie dans une cohorte nord-américaine contemporaine de patients adultes atteints d’un choc cardiogène. L’inexactitude de ses résultats pourrait faire en sorte qu’une assistance par ECMO serait refusée à des patients jugés comme présentant un risque élevé. D’autres études sont nécessaires pour valider d’autres modèles de prédiction pour les patients ayant besoin d’une ECMO-VA.